SPORTS PROGRAM INCLUDING PANCA SILATUS TO BE IMPLEMENTED IN IMPROVING KICKING SPEED IN ATHLETES - Hakim, Arif; Topo Yono; Ahmad Sulaiman (Gladi : Jurnal Ilmu Keolahragaan, 2025)
Pencak silat is not just a martial art, but also an effective medium in developing the physical, mental, and character of athletes. Intensive training focused on kicking techniques can accelerate motor reactions and increase explosiveness of movement, so that kicking speed can develop significantly. In addition to physical benefits, pencak silat also has a positive impact on mental and emotional aspects. This training helps athletes increase self-confidence, develop discipline, strengthen concentration, and hone stress management skills. The courage, perseverance, and never-give-up attitude instilled in each training session contribute to forming athletes who are tough, competitive, and ready to face challenges. Moreover, pencak silat also teaches fundamental values that support the formation of athlete character holistically. The philosophy of movement and training principles implemented in this program not only aims to improve competitive ability, but also instill integrity, sportsmanship, and high fighting spirit. Thus, the implementation of pencak silat in sports programs to increase athletes' kicking speed has a strategic value in forming individuals who are not only healthy and skilled, but also have character and are ready to compete at a higher level.